Release study on electrospun PVA/chitosan-based nanofibers loaded with Centella Asiatica extracts - Mohammad Rejab, Nur Farahanum; Wan Abdul Khodir, Wan Khartini; Bakhtiar, Muhammad Taher (2019)
Background: Centella asiatica (CA) extracts is proven to be beneficial for wound healing treatment as the active constituent which are asiaticoside, madecassoside and asiatic acid possesses several medicinal effects such as antioxidant and anti-inflammatory. However, too much CA can cause severe side effect.